Physiological Seed Performance of Local Aceh and National Release Variety of Rice (Oryza sativa L.) to Water Stress - Cut Nur Ichsan; . Bakhtiar; . Efendi; . Sabarudin (Syiah Kuala University, 2015)
Global warming causes changes in rainfall patterns causing lack of water for cultivation (IPPC,2007). About 50% of the rice cultivation area in the world has water shortages which becomes limiting factors of production (Bouman, 2009), hence the need early detection for drought- resistant varieties with seed physiological test. The experiment carry out at Laboratory Seed Technology and Industry of Agriculture Faculty Syiah Kuala University from April to June 2015. The experiment in split plot design 3X10 with 3 replication and standing roll wet paper germination method used. Amount of 2250 seed are used for physiological seed performance test. Water stress condition induced with PEG 6000 0%; 12.5%; 25%. Local genotype and national released variety of rice used in this experiment are Bo Santeut, Romokot, Sanbei, Pade mas, Aweuh, Inpari 16, IR 64, Situ Patenggang, and Towuti. Concentrations of Polyethilene Glicol 6000 (PEG 6000) have significant effect on all physiological parameter. Some local rice Aceh genotypes potentially to be cultivated on dry lands to cope water stress conditions.